The Concept, Process, And Form Of The Choreography Of The “Larung Segoro” Dance In The Petik Laut Traditional Ceremony : Larung Segoro dance is a group choreography that represents the local wisdom of Pasuruan City through the depiction of the Petik Laut traditional ceremony and the struggles of fishermen. The concept of this dance was developed through a long process using a symbolic approach that is evident in the movements, props, costumes, floor patterns, and music. This work has been performed in two forms: in an enclosed space (at the 2017 Dance Works Festival) and in an open space (as part of the Larungan procession), with adjustments made to suit the venue and atmosphere. The dance movements reflect the values of mutual cooperation, the life of fishermen, and expressions of gratitude to God. The researcher suggests that the government should be more proactive in providing information and documentation related to local culture, as well as promoting activities like Petik Laut. Further research is also hoped for on the traditional arts of Pasuruan City, which is rich in ethnic and cultural diversity. - Huda, Mokhamad Thoriqul; Yanuartuti, Setyo (Solah, 2025)
Larung Segoro dance is a dance piece created in 2017 at the East Java Provincial Dance Festival, representing the city of Pasuruan. Based on the event’s guidelines regarding the incorporation of local wisdom, this work highlights the concept of the Petik Laut Traditional Ceremony. This ceremony is held annually on a specific month and date. Larung Segoro Dance draws heavily on the values of the Petik Laut traditional ceremony to create a dance work, making it an intriguing subject for this research study. The objectives of this research include: 1) To describe the concepts and designs that the choreographer wishes to convey through the dance work “Larung Segoro.” 2) To analyze the form of performance in the dance work “Larung Segoro.” This study uses a qualitative descriptive method with data collection using observation, interviews, document study, and literature study techniques. The analysis involves data reduction, data presentation, and data validation. The results of this study indicate that the dance work Larung Segoro has undergone a very in-depth process. The closeness built by the choreographer in explaining the concept of the work and providing direct experience is a formative step in the creative process. The concepts and designs are embodied in the medium of movement, floor patterns, music, stage design, makeup, and costumes. One of the distinctive features of the Larung Segoro dance work lies in the props used. Replicas of a buffalo head and tumpeng (rice cone) are presented to create a realistic atmosphere, so that when the work is performed, it can effectively represent the activities and values contained in the traditional Petik Laut ceremony.